2014
DOI: 10.7897/2277-4343.05496
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study to Evaluate the Efficacy of Standard Fistulectomy Procedure and Kshar-Sutra Ligation in the Management of Fistula-in-Ano

Abstract: The disease, fistula in ano, which is considered to be a minor ailment, has high morbidity. Besides fistulectomy; the father of surgery, Sushruta, has also described its treatment in his text Sushruta samhita by kshar sutra method considering it as nadi vrana (wound with tract). The aim of the study was to compare the effectiveness, hospital stay, post operative pain between fistulectomy and kshar sutra procedure. 30 patients underwent fistulectomy and 30 patients underwent kshar sutra procedure according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Gouranga D et al; Gupta Shyam K et al and Shukla N et al had similar results. 2,4,6 In present study, no patient from seton treatment group developed incontinence for liquid/flatus/faeces. While 2 (10%) patients from fistulectomy group developed incontinence, one for flatus/liquids and one for faeces.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Gouranga D et al; Gupta Shyam K et al and Shukla N et al had similar results. 2,4,6 In present study, no patient from seton treatment group developed incontinence for liquid/flatus/faeces. While 2 (10%) patients from fistulectomy group developed incontinence, one for flatus/liquids and one for faeces.…”
Section: Discussionmentioning
confidence: 44%
“…Gupta Shyam K et al studied 60 patients of fistula-in-ano and reported recurrence of 3.33% with medicated seton and 10% recurrence with fistulectomy. 6 Shukla N et al in their study reported recurrence of 4% with medicated seton and 11% recurrence with fistulectomy. 4 Post-operative pain was assessed at 6hr, 24 hr and 48 hr on a visual analogue scale.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…There is simultaneous cutting and healing of the tract and no pocket of pus is allowed to stay back. 19 Thus it provides an environment for healthy granulation tissue to develop providing an avenue for nadivrana (sinuses) to heal completely. Further application of ksharasutra was described by Sushruta as direction of the sinus should first be ascertained by a probe.…”
Section: Ayurvedic View About Sinus and Ksharasutramentioning
confidence: 99%
“…So kshara are not only cause the destruction (lysis)of unhealthy tissue but also help in their debridement. Hence this is an ideal procedure to be adopted for the management of sinus track as it not only destroy the fibrous wall of track as it not only destroys the fibrous wall of track but help in its curettage.There is simultaneous cutting and healing of the tract and no pocket of pus is allowed to stay back [13] . Thus it provides an environment for healthy granulation tossue to develop providing an avenue for nadivrana(sinuses) to heal completely.further application of ksharsutra was described by a probe.A ksharsutra was described by Sushruta as direction of the sinus should first be ascertained into the track and brought out from the other end with the help of probe.The two ends of the thread should be firmly tied together.Anather ksharsutra should adopt a similar procedure in case fistula-in-ano [14] .…”
mentioning
confidence: 99%